Desarrollo del portafolio de servicios para consultoría, extensión e investigación a partir de las unidades de procesos industriales y laboratorios disponibles en el Centro de Procesos e Innovación para la Industria Sostenible (CEPIIS). (2024)
The development of the portfolio of services for the Center for Processes and Innovation for Sustainable Industry (CEPIIS) of the University of America is carried out as a need to know the services that can be offered in the semi-industrial plant, to acquire information for recognition and identification of the structural and operational process units. This must offer consulting, extension and research services to the industry of scalable units through the characterization and requirements for the start-up of the plant. Being that the differentiating services to be offered will solve the trend needs of the current industry, taking into account operational logistics criteria and prevention of corresponding risks to generate reliability by the implementation of equipment and facilities to the collaborators who are in the workplace. Through the Sustainable Development Goals (SDG) addressed, starting with the fourth one which talks about quality education, it is mentioned that one of its goals is to increase the number of technical or professional people who have sufficient skills required to have job opportunities, thus, through the portfolio of services offered by CEPIIS, it can provide practical learning to undergraduate or graduate students, teachers and professionals interested in carrying out projects at the plant; and as for the eighth objective which is about decent work and economic growth, one of the proposals made in this is to achieve high levels of productivity in terms of the economy taking into account technology and innovation, for which it relates to the plant to generate employment opportunities in the sector, in addition to carrying out consultancies through expert advice to companies, and complying with the innovation parameter through research developed in projects for the chemical industry.